Estimation of Center of Mass Displacement Based on Gait Analysis - Xiaoli Meng; Shuyan Sun; Lianying Ji; Jiankang Wu; Wai-Choong Wong (2011 International Conference on Body Sensor Networks, 2011)
This paper proposes an ambulatory algorithm to estimate Center of Mass (CoM) displacement of the subjects for Micro-sensor Motion Capture (MMoCap) system. Estimation of the CoM displacement is based on gait analysis and segmental kinematics. In our MMoCap system, the human body is modeled as a kinematic chain of rigid segments linked by joints, and the pelvis is considered as the root joint in the model. Each joint's relative positions are obtained from hierarchical transformations. The CoM displacement is imported into the root joint of a human skeleton model to track human locomotion with reference to the global coordinate system. Performance of the algorithm is evaluated using simulated sensor data obtained from an optical motion capture database and also by our ambulatory MMoCap system. The experimental results show robust and continuous tracking of CoM movements while a subject is walking.